PENGARUH NILAI PELANGGAN, HARGA, KEBUTUHAN MENCARI VARIASI, HAMBATAN BERPINDAH, DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PERPINDAHAN MEREK Pengguna Kartu Prabayar IM3 PT. Indosat (Studi pada Mahasiswa Universitas Stikubank Semarang) - Mirna Novita Arifina, 11.05.51.0049 (Students Journal of Economic and Management, 2016)
The purpose of this study to analyze the influence of customer value, price, variety seeking, switching barriers and celebrity endorser of the brand switching decision IM3 prepaid card users. The population of this research is Stikubank Semarang University student who had done IM3 brand switching. The sampling technique used in this study is convenience sampling with a sample of 100 respondents. Analysis of the data in this study using multiple regression. The results showed that the value of the customer, the price, variety seeking, switching barriers and celebrity endorser positive and significant impact on brand switching decision. This study has the limitations of the limited sample as one of the principal sources of data, which is limited only to the students of the University Stikubank ever did IM3 brand switching, besides the variables used in the study is limited to variable customer value, price, variety seeking, switching barriers and celebrity endorser. There may be other factors that have more influence in the decision making on brand switching IM3 prepaid cards, such as low levels of satisfaction, product attributes, and others. Keywords : Customer Value, Price, Variety Seeking, Switching Barriers, Celebrity Endorser, and Brand Switching.